AN ANALYSIS ON CODE SWITCHING AND CODE MIXING USED BY THE ENGLISH LECTURERS IN THE CLASSROOM INTERACTION - Anis Riskiyana (The Ellite of Unira, 2019)
As bilingual speakers the English lecturers give explanation and instruction by using their languages freely. They tend to switch code as well as mix code between two languages (Indonesian-English or vice versa) in order to create an effective strategy of communication in the classroom. This study described the forms of code switching applied in clause, tag, filler, interjection, and the forms of code mixing applied in word and phrase through Fasold and Holmes’ theory. The implementation of them was based on the position (as translation and without translation).